Productivity and efficiency differences between Czech and Slovak milk producers - Lukas Cechura; Heinrich Hockmann; Zdenka Mala; Michal Maly (Review of Agricultural and Applied Economics, 2014)
The paper deals with the analysis of productivity and efficiency differences between Czech and Slovak milk producers. The estimate of stochastic metafrontier multiple output distance function revealed that both Czech and Slovak milk producers highly exploit their production possibilities. On the other hand, productivity differences were pronounced. The Slovak regions were found being falling behind. Only the West Slovak regions can keep pace with competitors. The Central Bohemia and Moravian-Silesian regions are the most productive regions. We found that technical efficiency and management component are the most important factors determining the regional differences.
Keywords: D24; O12; P27; 330; milk production; productivity; efficiency; metafrontier analysis; SFA